Gene Flow from Transgenic PPO-inhibiting Herbicide-resistant Rice to Weedy Rice, and Agronomic Performance by Their Hybrids - Nam, Kyong-Hee; Kim, Do Young; Moon, Ye Seul; Pack, In Soon; Jeong, Soon-Chun; Park, Kee Woong; Kim, Chang-Gi (Journal of plant biology = Singmul Hakhoe chi, 2019)
Hybridization of transgenic crops with their weedy relatives may spread transgenes into weedy populations and alter the ecological fitness of such hybrids. Our study objective was to quantify the rate of gene flow from herbicide-resistant transgenic rice to weedy rice and compare the performance of hybrids between them over several generations. The transgenic plants used in these experiments are resistant to protoporphyrinogen IX oxidase (PPO)-inhibiting herbicides such as oxyfluorfen, oxadiazon, and butafenacil. The rate of gene flow from those plants to five weedy accessions ranged from 0.025% to 0.139%. The F 1 hybrids that resulted from gene flow from transgenic to weedy rice and subsequent F 2 progeny were shorter than the weedy parents but produced significantly more and heavier grains. The F 3 progeny resulting from gene flow were resistant to oxyfluorfen, which indicated that the gene associated with PPO-inhibiting herbicide resistance is dominantly inherited. The GR 50 values (dose required for 50% shoot fresh weight reduction) for F 3 progeny were > 69-fold greater than for the weedy rice. These results suggest that transgenes that could escape from PPO-inhibiting herbicide-resistant rice and be transferred to weedy rice might persist and disperse into weedy populations over several generations due to herbicide resistance and improved reproductive traits in the hybrids.